Bipolar Conduction and Giant Positive Magnetoresistance in Doped Metallic Titanium Oxide Heterostructures. Issue 9 (3rd February 2021) - Huang, Ke; Wang, Tao; Jin, Mengjia; Wu, Liang; Wang, Junyao Floria; Li, Shengyao; Qi, Dong‐Chen; Cheng, Shuying; Li, Yangyang; Chen, Jingsheng; He, Xiaozhong; Li, Changjian; et al.
Abstract: Empowering conventional materials with unexpected magnetoelectric properties is appealing to the multi‐functionalization of existing devices and the exploration of future electronics. Recently, owing to its unique effect in modulating a matter's properties, ultra‐small dopants, for example, H, D, and Li, attract enormous attention in creating emergent functionalities, such as superconductivity, and metal–insulator transition. Here, an observation of bipolar conduction accompanied by a giant positive magnetoresistance in D‐doped metallic Ti oxide (TiO x D y ) films is reported. To overcome the challenges in intercalating the D into a crystalline oxide, a series of TiOx Dy is formed by sequentially doping Ti with D and surface/interface oxidation. Intriguingly, while the electron mobility of the TiO x D y increases by an order of magnitude larger after doping, the emergent holes also exhibit high mobility. Moreover, the bipolar conduction induces a giant magnetoresistance up to 900% at 6 T, which is ≈6 times higher than its conventional phase. This study paves a way to empower conventional materials in existing electronics and induce novel electronic phases. Abstract : Tuning the electrical properties is critical for novel electronic applications. In this work, high‐mobility bipolar conduction is achieved in an originally electron‐conducting titanium oxide (TiO x ) through deuterium doping. This bipolar conduction leads to a giant magnetoresistance. The results demonstrate the feasibility of tuning carriers with ultra‐small dopants and pave a way for future high‐speed bipolar electronics.